Analysis of Health Law Relating to Health Services Affected by COVID-19 - Andi Puji Kristanto (Journal La Sociale, 2021)
COVID-19 has a profound influence on all aspects of life, especially in the medical field. Services for public health who are not tainted with COVID-19 have similar issues. As a result, the writers want to look at health legislation and how it relates to the status of health care after the COVID-19 pandemic. In this study, qualitative approaches were used for a descriptive methodology. According to the findings of the investigation, COVID-19 has caused significant damage to medical and hospital staff, resulting in numerous problems for health care, especially while coping with COVID-19 patients and patients who are not contaminated with COVID-19. This is obviously in conflict with current health legislation, which recognizes health as one of the most fundamental human needs and has newly been granted statutory protection. The government has formulated numerous strategies in this regard so that this fundamental right can be battled for even throughout the pandemic.